An in-Depth Investigation into the Impact That Awards and Recognition Have on the Performance of Staff Members - Burhaini Burhaini; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine the relationship between employee awards and performance. This investigation made use of publicly available information in its design, technique, and approach. Internet search engines and connected periodicals were used to compile the secondary data. In order to back up the research, the necessary textbooks were reviewed. Both monetary and non-monetary incentives have an effect on workers' productivity, according to the studies that have been done. In contrast to the long-term effects of intrinsic rewards, the short-term effects of extrinsic rewards on employee behavior are widely acknowledged. Research Originality and Theory Contribution: This study adds to the body of knowledge on the topic of total incentives, which encompass monetary and non-monetary rewards, by deepening our comprehension of how these programs affect employee performance. Management Implications: This study's results will help workers and bosses understand the power of employee rewards to boost productivity. Research Limitations and Implications: The researcher in this study had no means of verifying the reliability of the data since the study relied entirely on secondary sources.